PENGARUH RASIO KEUANGAN TERHADAP KINERJA KEUANGAN BANK SYARIAH - Saiful Bachri; . Suhadak; Muhammad Saifi (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
This study aims to obtain empirical evidence about the effect of the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Operational Efficiency Ratio (OER) and the Financing to Deposit Ratio (FDR) to the Return On Assets (ROA) and to determine the variable that give the dominant influence on the profitability of Islamic banks. The populations used in this study were all Islamic Banks operating in Indonesia. Purposive sampling was used a sampling method, obtaining three Islamic Banks. Secondary data was used as a form of financial statements quarterly publicized; starting from the first quarter of 2009 to the third quarter of 2012. The data analyses employed the use of multiple linear regression approach. The results of this study indicate that the variable Operational Efficiency Ratio (OER) has a significant influence on the Return on Assets (ROA) with a significance level of 0,000. While, the variable Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) and the Financing to Deposit Ratio (FDR) did not significantly affect to the Return on Assets (ROA) with a significance level of each variable of 0,641 (CAR), 0,166 (NPF) and 0,440 (FDR). Variable that affect dominantly to the Return on Assets (ROA) is the Operational Efficiency Ratio (OER) with a beta value of 0,563. Keywords: Financial Ratios, Financial Performance